Public finance and full employment - Musgrave, Richard A.; Domar, Evsey D.; Robinson, Roland I. (Washington : Board of Governors of the Federal Reserve System, 1945)
The benefits of taxation for public revenues and expenditure planning.
Text on p. [2] of cover.
sju 22/01/2019
Loans
Keywords: Finance